Unidos pelo rio, separados pela ponte: desigualdades entrelaçadas na fronteira franco-brasileira - Fabio Santos (Confins)
Besides analyzing the steps that led to the delay and the inauguration of the Binational Bridge, this article seeks to understand the effects of the bridge four years after its inauguration. Based on six months of ethnographic fieldwork as well as document and discourse analysis, the article reinforces the argument that the issue of visa non-reciprocity has not only been key to the delay of the bridge: in the aftermath of the inauguration, it actually turned the bridge into a one-way street which perpetuates inequalities on the basis of citizenship and in connection with other axes of stratification. Causing conflicts in a historically entangled region, the Binational Bridge contradicts prevailing political framings of a connecting bridge.